2010
DOI: 10.1016/j.exger.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ageing and rejuvenating effects of quercetin

Abstract: Homeostasis is a key feature of the cellular lifespan. Its maintenance influences the rate of ageing and it is determined by several factors, including efficient proteolysis. The proteasome is the major cellular proteolytic machinery responsible for the degradation of both normal and damaged proteins. Alterations of proteasome function have been recorded in various biological phenomena including ageing and replicative senescence. Proteasome activities and function are decreased upon replicative senescence, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(92 citation statements)
references
References 54 publications
1
91
0
Order By: Relevance
“…The observed dependence is in agreement with studies in human (10,15,27) and yeast cells (7,32) and in multicellular organisms (8,46,55,58). It is, however, noteworthy that with the exception of quercetin (10) and 18a-GA (27) in all other mentioned studies, proteasome activation was achieved through genetic manipulation.…”
Section: Discussionsupporting
confidence: 78%
“…The observed dependence is in agreement with studies in human (10,15,27) and yeast cells (7,32) and in multicellular organisms (8,46,55,58). It is, however, noteworthy that with the exception of quercetin (10) and 18a-GA (27) in all other mentioned studies, proteasome activation was achieved through genetic manipulation.…”
Section: Discussionsupporting
confidence: 78%
“…In combination with quercetin, a plant flavonoid with lifespan-extending antioxidant and proteosome activating properties in worms 157160 and cytoprotective effects in mice 161 , dasatinib exhibits senolytic activity in cultured cells. In old mice, these compounds were shown to improve parameters of cardiac and vascular function, although the extent to which senescent cell killing occurred and contributed to these effects is unknown.…”
Section: Therapy-induced Senescencementioning
confidence: 99%
“…Interestingly, recessive mutation of the gene age-1 or daf-2 (encoding for the IGF-1 receptor in C. elegan ), two key players in the metabolic pathway to regulate the rate of aging, abolished the lifespan-extension effect of quercetin in C. elegans [58,59], suggesting that quercetin may prolong lifespan in the worms through inhibiting, either directly or indirectly, the age-1 and daf-2-mediated pathways. A recent study reported that quercetin and its derivative quercetin caprylate can rejuvenate senescent fibroblasts and increase their lifespan via activating proteasome [60]. Quercetin is reported as the most potent reactive oxygen species (ROS) scavenger of ROS in the flavonoid family and quercetin has over 6 times the antioxidant capacity than the reference antioxidant trolox or vitamin C [6163].…”
Section: Antiaging Phytochemicalsmentioning
confidence: 99%